Investigating the Performance of Rechargeable Zinc-Air Fuel Cell - H.Shallal, Ahmed; Shakir , Ibtehal Kareem (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
Zinc-air fuel cells (ZAFCs) are a promising energy source that could compete with lithium-ion batteries and perhaps proton-exchange membrane fuel cells (PEMFCs) for next-generation electrified transportation and energy storage applications. In the present work, a flow-type ZAFC with mechanical rechargeable was adopted, combined with an auxiliary cell (electrolyzer) for zinc renewal and electrolyte recharge to the main cell. In this work a practical study was performed to calculate the cell capacity (Ah), as well as study the electrolysis cell efficiency by current efficiency, and study the effective parameters that have an influence on cell performance such as space velocity and current density. The best parameters were selected to obtain the best performance for cell operation. The obtained cell capacity was 2.4Ah. The best performance of the electrolyzer was obtained with 0.6min-1 space velocity. At the same time, the best performance of the electrolyzer was when the value of the current density was 200A/m2